Luminescent properties and X-ray imaging result of Lu2O3:Eu structured scintillation film on YSZ single crystal substrate by LCVD method. Issue 20 (15th October 2021) - Hu, Juan; Guo, Han; Du, Wenbin; Yang, Fan; Yang, Qiuhong; Feng, He
Abstract: Micro-columnar structured europium doped lutecia (Lu2 O3 :Eu) scintillation film is one of the most attractive candidate materials for high-energy hard X-ray imaging detectors because of their excellent physical, scintillation properties and light guide effect. Lu2 O3 :Eu micro-columnar film (MCF) with 9 μm thickness was obtained on a yttrium stabilized zirconia (YSZ) (100) single crystal substrate by laser chemical vapor deposition (LCVD), and its structure, morphology, photoluminescence and scintillation properties were characterized. The structure and morphology of obtained film were investigated by grazing incidence X-ray diffraction (GIXRD) and scan electron microscopy (SEM). The photoluminescence and scintillation properties, including photoluminescence excitation (PLE), photoluminescence (PL), PL decay, X-ray excited luminescence (XEL), were measured and discussed. The X-ray imaging result of Lu2 O3 :Eu MCF on YSZ substrate was obtained for the first time and spatial resolution of 2 μm was obtained at BL13W beamline at Shanghai synchrotron radiation facility (SSRF).